Sediment solid phase characteristics on the Amazon shelf obtained in April/May 2021 during RV METEOR cruise M174 - Choisnard, Noémie; Moros, Matthias; Voss, Maren (PANGAEA, 2023)
The Amazon River is known as a region of intense biochemical reactivity. As a result of increased anthropogenic impacts in its catchment (e.g. population growth, agriculture, and deforestation), The Amazon River is undergoing fundamental changes. The RV METEOR cruise M174 (https://doi.org/10.1594/PANGAEA.935041) aimed to provide an integrated overview of nitrogen cycling processes in areas influenced by the Amazon River, which is crucial to estimate the ecosystem's health and productivity. During this cruise, a MUC was deployed at eight stations to collect short sediment cores, in order to explore the influence of the river on sediments. This dataset presents the results of sediment solid phase characteristics from the surface sediment down to 30 cm depth.
Keywords: Amazon River; Benthic fluxes; M174; nitrogen; nitrous oxide; porewater; sediment